"The difference being a woman made" Untold Lives in personal and intellectual context. Issue 3 (19th July 2017) - Rutherford, Alexandra; Milar, Katharine
Abstract: To mark the 30th anniversary of the publication of Scarborough and Furumoto's classic work Untold Lives, and to honor the intellectual legacy of Elizabeth Scarborough (1935–2015), we introduce this special issue devoted to the histories of women, gender, and feminism in psychology. We provide a short biographical sketch of Elizabeth, highlighting her own marriage‐career dilemma, then contextualize the publication of Untold Lives within the historiography on women in psychology at that time. We conclude by discussing intersectionality as an analytic framework for the history of psychology as a way to extend and enrich this historiography.